Pengaruh Tipe Kepribadian Big Five terhadap Gaya Kepemimpinan Transformasional Karyawan PT Arta Boga Cemerlang Surabaya - Sudjiwanati - (Jurnal Aplikasi Manajemen, 2012)
In the changes era many entrepreneur, have already realized that succeed or not their effort to increase the quality of production depend on human resources substance that do the job and operate the tool work. Human resources as an employee on the company have characteristic type of personality, thought, feeling and willingness on work. Big five personality type can be used variativally to understand their employee condition on the changes era through the leadership approach that appropriate with their employee condition. The appropriate leadership to lead their employee on the great distribution of division should be used an transformational leadership approach. A result of the research show that there is an influence of the big five personality type with transformational leadership.Keywords: Transformational leadership, Big five personality type